Myogenic programs of mouse muscle cell lines: expression of myosin heavy chain isoforms, MyoD1, and myogenin (The Rockefeller University Press, 1990)
Different mouse muscle cell lines were found to express distinct patterns of myosin heavy chain (MHC) isoforms, MyoD1, and myogenin, but there appeared to be no correlation between the pattern of MHC expression and the patterns of MyoD1 and myogenin expression. Myogenic cell lines were generated from unconverted C3H10T1/2 cells by 5- azacytidine treatment (Aza cell lines) and by stable transfection with MyoD1 (TD cell lines) or myogenin (TG cell lines). Myogenic differentiation of the newly generated cell lines was compared to that of the C2C12 and BC3H-1 cell lines. Immunoblot analysis showed that differentiated cells of each line expressed the embryonic and slow skeletal/beta-cardiac MHC isoforms though slow MHC was expressed at a much lower, barely detectable level in BC3H-1 cells. Differentiated cells of each line except BC3H-1 also expressed an additional MHC(s) that was probably the perinatal MHC isoform. Myogenin mRNA was expressed by every cell line, and, with the exception of BC3H-1 (cf., Davis, R. L., H. Weintraub, and A. B. Lassar. 1987. Cell. 51:987-1000), MyoD1 mRNA was expressed by every cell line. To determine if MyoD1 expression would alter the differentiation of BC3H-1 cells, cell lines (termed BD) were generated by transfecting BC3H-1 cells with MyoD1 under control of the beta-actin promoter. The MyoD1 protein expressed in BD cells was correctly localized in the nucleus, and, unlike the parental BC3H-1 cell line that formed differentiated MHC-expressing cells, which were predominantly mononucleated, BD cell lines formed long, multinucleated myotubes (cf., Brennan, T. J., D. G. Edmondson, and E. N. Olson. 1990. J. Cell. Biol. 110:929-938). Despite the differences in morphology and MyoD1 expression, BD myotubes and the parent BC3H-1 cells expressed the same pattern of sarcomeric MHCs.